The Process of "Urbanization" in the Countryside: A Study of Huron and Bruce Counties, 1891-1981 - Dahms, Fred (Urban History Review / Revue d'histoire urbaine, 1984)
A broad interpretation of urban history as "process" is proposed to include the temporal study of small settlements within the context of their agricultural hinterlands and urban systems. The illustrative case study of eight places in Huron and Bruce Counties, Ontario, between 1891 and 1981 documents the process of increasing functional specialization and "urbanization" of settlements having populations under 1,100 in 1981. Field surveys in 1981 and census data since 1961 contradict the popular perception of "dying villages" based primarily upon directory tabulations and earlier population trends. Most of the eight places surveyed have experienced recent population growth and much less functional decline than suggested by either directories or central place literature. Local specialized economic functions and environmental attractions have contributed substantially to their continuing and increasing viability.